2009
DOI: 10.1074/jbc.m809235200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Extracellular Acidosis on the Release and Dispersal of Soluble and Membrane Proteins Secreted from the Weibel-Palade Body

Abstract: Proteins secreted from Weibel-Palade bodies (WPBs) play important roles in regulating inflammatory and hemostatic responses. Inflammation is associated with the extracellular acidification of tissues and blood, conditions that can alter the behavior of secreted proteins. The effect of extracellular pH (pH o ) on the release of von Willebrand factor (VWF), the VWFpropolypeptide (Proregion), interleukin-8, eotaxin-3, P-selectin, and CD63 from WPBs was investigated using biochemical approaches and by direct optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 35 publications
(45 reference statements)
3
44
0
3
Order By: Relevance
“…ssEGFP mobilities were the same in both cell types (P0.19). Coexpression of ProVWF-mRFP did not change D (P0.31; (Erent et al, 2007) it will not interact strongly with ProVWF (Babich et al, 2009;Hannah et al, 2005). Consistent with this, Proregion-EGFP was significantly more mobile than ProVWF-EGFP (P<10 -4 ).…”
Section: Wpb Core Proteins Are Mobile In the Er Of Huvecssupporting
confidence: 71%
See 4 more Smart Citations
“…ssEGFP mobilities were the same in both cell types (P0.19). Coexpression of ProVWF-mRFP did not change D (P0.31; (Erent et al, 2007) it will not interact strongly with ProVWF (Babich et al, 2009;Hannah et al, 2005). Consistent with this, Proregion-EGFP was significantly more mobile than ProVWF-EGFP (P<10 -4 ).…”
Section: Wpb Core Proteins Are Mobile In the Er Of Huvecssupporting
confidence: 71%
“…These data suggest that immobilisation is unlikely to be due to a specific interaction between P-selectin and Proregion or VWF per se, but rather to the presence of the Proregion-VWF paracrystal. Consistent with this is the dramatic slowing of P-selectin release during WPB exocytosis under conditions that prevent complete collapse of the Proregion-VWF paracrystal, as indicated by retention of the rod-like WPB morphology (Babich et al, 2009). Analysis of P-selectin-EGFP mutants in WPBs of HUVECs and HEK293 cells showed that immobilisation depends on the size of the extracellular domain.…”
Section: P-selectin-egfp Immobilisation In Wpbs Requires the Proregiosupporting
confidence: 48%
See 3 more Smart Citations